The Impact of Dialysis Modality on Left Ventricular Function in Patient with End Stage Kidney Disease - Maskey, Abhishek; Paudel, Navaraj; Sapkota, Subash; Jha, Pooja (Nepal Journal of Medical Sciences, 2020)
Introduction: Cardiovascular disease is frequent in end-stage kidney disease patients, and is a major cause of morbidity and mortality. This study was carried out to assess the comparative cardiac effects of hemodialysis and continuous ambulatory peritoneal dialysis on left ventricular function. Methods: A prospective observational study was carried out in patients undergoing hemodialysis or continuous ambulatory peritoneal dialysis at least for 6 months. The duration of the study was from June 2019 to May 2020. CAPD consists of 3 to 4 exchanges/day and haemodialysis 2-3 times/week for 4 hours. Baseline characteristics age, gender, dialysis duration, hypertension, diabetes and hyperlipidaemia were collected. The same cardiologist performed all echocardiography at the end of hemodialysis session in hemodialysis patients and after the drain of dialysate in peritoneal dialysis patients. Results: Sixty patients (40 hemodialyses, 20 peritoneal dialyses) were enrolled. The mean age of the patient was 53.71±13.00 years (range 25-76). There was a slightly higher number of male in the hemodialysis group (p= 0.065). Systolic and diastolic blood pressure were significantly higher in hemodialysis groups (p<0.001). Regarding left ventricular parameters, hemodialysis patients had a higher prevalence of left ventricular diastolic dysfunction, left ventricular hypertrophy, left ventricular mass compared to peritoneal dialysis patients. Pericardial effusion and thickening were present higher in hemodialysis patients and was statistically significant (p<0.05). Conclusion: The modality of dialysis influence left ventricular function. Left ventricle dysfunction is prevalent among hemodialysis patients compared to peritoneal dialysis. Echocardiographic follow up is essential as this could improve the management of cardiovascular complications in dialysis patients.